Early Skin-to-Skin Contact Does Not Affect Cerebral Tissue Oxygenation in Preterm Infants <32 Weeks of Gestation - Kathrin Hanke; Tanja K. Rausch; Runa Sosnowski; Pia Paul; Juliane Spiegler; Mirja Müller; Inke R. König; Wolfgang Göpel; Egbert Herting; Christoph Härtel (Children, 2022)
Aim: It was the aim of our study to determine the regional cerebral tissue oxygenation saturation (rcSO2) as an additional monitoring parameter during early skin-to-skin contact (SSC) in preterm infants with a gestational age of <32 gestational weeks. Methods: We conducted two observational convenience sample studies using additional monitoring with near-infrared spectroscopy (NIRS) in the first 120 h of life: (a) NIRS 1 (gestational age of 26 0/7 to 31 6/7 weeks) and (b) NIRS 2 (gestational age of 24 0/7 to 28 6/7 weeks). The rcSO2 values were compared between resting time in the incubator (period I), SSC (period II) and handling nursing care (period III). For the comparison, we separated the sequential effects by including a “wash-out phase” of 1 h between each period. Results: During the first 120 h of life 38/53 infants in NIRS 1 and 15/23 infants in NIRS 2 received SSC, respectively. We found no remarkable differences for rcSO2 values of NIRS 1 patients between SSC time and period I (95% confidence interval (CI) for the difference in %: SSC vs. period I [1; 3]). In NIRS 2, rcSO2 values during SSC were only 2% lower compared with period I [median [1. quartile; 3. quartile] in %; 78 [73; 82] vs. 80 [74; 85]] but were similar to period III [78 [72; 83]]. In a combined analysis, a small difference in rcSO2 values between SSC and resting times was found using a generalized linear mixed model that included gender and gestational age (OR 95% CI; 1.178 [1.103; 1.253], p < 0.0001). Episodes below the cut-off for “hypoxia”; e.g., <55%, were comparable during SSC and periods I and III (0.3–2.1%). No FiO2 adjustment was required in the vast majority of SSC episodes. Conclusions: Our observational data indicate that rcSO2 values of infants during SSC were comparable to rcSO2 values during incubator care and resting time. This additional monitoring supports a safe implementation of early SSC in extremely preterm infants in NICUs.